2004
DOI: 10.1002/elsc.200420021
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Removal of Phenol and Chlorophenols Using Soybean Seed Hulls

Abstract: Soybean peroxidase (SBP), (EC 1.11.1.7) can be readily extracted from soybean seed hulls. This study reports on the direct use of soybean seed‐hull extracts for the bioremediation of phenolic wastes. The crude SBP extract from the hulls, like pure soybean peroxidase, is catalytically active in a broad range of pH and temperatures. As SBP is gradually released into the aqueous solution from seed hulls, the direct use of soybean seed hulls can reduce SBP inactivation by H2O2 and enhance the utilization efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
3
16
0
4
Order By: Relevance
“…Similar results were reported for SBP, which showed pH optima between 5.5 and 8 when used for the removal of a variety of chlorophenols (Caza et al 1999). By contrast, other investigations indicated that SBP was more effective in removing certain phenols from artificial waste water at pH 9 (Wright andNicell 1999), 8.2 (Kennedy et al 2002) and 7 (Bassi et al 2004). Removal of chlorophenols from model media using TNP and BGP was shown to be optimal within a pH range 5-7 (Duarte-Vázquez et al 2002) and 5-6 (Akhtar and Husain 2006), respectively.…”
Section: The Effect Of H 2 O 2 Ph and Temperaturesupporting
confidence: 82%
“…Similar results were reported for SBP, which showed pH optima between 5.5 and 8 when used for the removal of a variety of chlorophenols (Caza et al 1999). By contrast, other investigations indicated that SBP was more effective in removing certain phenols from artificial waste water at pH 9 (Wright andNicell 1999), 8.2 (Kennedy et al 2002) and 7 (Bassi et al 2004). Removal of chlorophenols from model media using TNP and BGP was shown to be optimal within a pH range 5-7 (Duarte-Vázquez et al 2002) and 5-6 (Akhtar and Husain 2006), respectively.…”
Section: The Effect Of H 2 O 2 Ph and Temperaturesupporting
confidence: 82%
“…Similar results were reported for SBP, which showed pH optima between 5.5 and 8 when used for the removal of a variety of chlorophenols [16]. By contrast, other investigations indicated that SBP was more effective in removing certain phenols from artificial waste water at pH 9 [28], pH 8.2 [19] and pH 7 [32]. Removal of chlorophenols from model media using TNP and BGP was shown to be optimal within a pH range 5-7 [30] and 5-6 [31], respectively.…”
Section: Effect Of Phsupporting
confidence: 80%
“…Recombinant protein expression and protein engineering (Asad et al, 2011;Grigorenko et al, 1999;Morawski et al, 2000) have been implemented in some of these cases. For some applications, crude SBP may be sufficient or preferred such as in waste water treatment (Bassi et al, 2004;Flock et al, 1999;Wilberg et al, 2002) or as a biocatalyst in organic synthesis (Bouldin et al, 2011;Velde et al, 2001), whereas higher value commodities such as diagnosis tests and therapeutics would require more costly alternatives such as purified or recombinant peroxidases. HRP and SBP have very similar three-dimensional structure with 57% sequence homology (Kamal and Behere, 2003).…”
Section: Introductionmentioning
confidence: 99%